Does text generation improve learning from expository text? A conceptual replication attempt - Julia Schindler; Tobias Richter (Cognitive Research, 2025)
Abstract The aim of the present study was to test the replicability of the text generation effect for learning with expository texts while systematically varying contextual factors that—based on extant literature—can be assumed to affect the occurrence and magnitude of the text generation effect. Seven experiments were conducted in which participants either read (control condition) or unscrambled sentences (generation condition) in expository texts. The experiments varied systematically on intentionality of learning, learning time constraint, retention interval, and study design. Contrary to expectations, no text generation effect could be found. Instead, some of the experiments even revealed a learning disadvantage for text generation compared to the reading control condition. In only one experiment (Experiment 6) and for just one of the learning measures, learners performed better when they had generated the texts. In sum, the results indicate that a generation effect is most likely to occur when learning is intentional, when learning time is unrestricted, and for immediate testing. The findings suggest that the applications of text generation in educational contexts are rather limited.